2005
DOI: 10.1128/jcm.43.12.6098-6107.2005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Virulence Genotype with Phylogenetic Background in Comparison to Different Seropathotypes of Shiga Toxin-Producing Escherichia coli Isolates

Abstract: , stx 2-vha , and stx 2-vhb ) were concentrated in seropathotypes associated with disease, others (astA, HPI, stx 1c , and stx 2-NV206 ) were concentrated in seropathotypes that are not associated with disease. Taken together with the observation that the STEC-A group was exclusively composed of strains lacking eae recovered from seropathotypes that are not associated with disease, the "atypical" virulence pattern suggests that STEC-A strains comprise a distinct category of STEC strains. A practical benefit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 54 publications
10
60
1
5
Order By: Relevance
“…A striking phylogenetic distribution of the PAI I CL3 genotypes could explain this distinction. While six major phylogenetic groups of E. coli (A, B1, C, E, D and B2) form the core of the E. coli species (Escobar-Paramo et al, 2004), we showed in a previous study that LEE-negative STEC strains in seropathotype C belong exclusively to the ECOR group B1 (Girardeau et al, 2005). Therefore, the observed link between complete PAI I CL3 genotype and seropathotype C demonstrates a striking phylogenetic link between intact PAI I CL3 and ECOR group B1.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A striking phylogenetic distribution of the PAI I CL3 genotypes could explain this distinction. While six major phylogenetic groups of E. coli (A, B1, C, E, D and B2) form the core of the E. coli species (Escobar-Paramo et al, 2004), we showed in a previous study that LEE-negative STEC strains in seropathotype C belong exclusively to the ECOR group B1 (Girardeau et al, 2005). Therefore, the observed link between complete PAI I CL3 genotype and seropathotype C demonstrates a striking phylogenetic link between intact PAI I CL3 and ECOR group B1.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have demonstrated that determination of the seropathotype distribution of virulence factors allows identification of DNA targets for selective detection of strains that present a risk to public health (Gilmour et al, 2006;Karmali et al, 2003). As we have shown, there is a link between seropathotype, prevalence of various virulence factors, phylogeny and Shiga toxin gene expression (de Sablet et al, 2008;Girardeau et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A correlation has been observed between the stx 2 genotype and severity of disease, as several studies have shown that some stx 2 subtypes are frequently associated with a higher risk of developing HUS, whilst others are present mainly in strains isolated from patients with uncomplicated diarrhoea or in those not isolated from humans (Eklund, et al, 2002;Friedrich et al, 2002;Zhang et al, 2002;Jenkins et al, 2003;Leung et al, 2003;Beutin et al, 2004;Girardeau et al, 2005;Bielaszewska et al, 2006;Persson et al, 2007). By applying the recently proposed nomenclature to previous studies, it is possible to correlate stx 2a with high virulence and HUS, and stx 2e , stx 2f and stx 2g with low pathogenicity in humans.…”
Section: Shiga Toxin Subtypesmentioning
confidence: 99%